Experience of Coping Mechanisms in Dealing with Stressful Conditions in People Living with HIV/AIDS in The Bojonegoro Community Health Center Area - Ardha Wahyuning Tyas; Ahmad Zainal Abidin; Teguh Subagyo (PT Bukuloka Literasi Bangsa, 2025)
The number of people with Human Immunodeficiency Virus / Acquired Immune Deficiency Syndrome is increasing every year. Some examples of causes are having sex with people with HIV/AIDS, the use of non-sterile syringes, and an HIV/AIDS-positive mother who is pregnant. This can threaten life on a bio-psycho-social and spiritual level. The purpose of this study is to explore the experience of coping mechanisms in dealing with stress conditions in people diagnosed with HIV/AIDS. This study uses a qualitative design with a phenomenological approach. The sampling technique used is purposive sampling with data- al analysis using the Creswell method. Four people participated in this study. The results of this study reveal five themes. The conclusion of this study is that patients have coping mechanisms such as finding solutions to the problems they experience, namely Problem Focus Coping and Emoticons Focus Coping. Where Problem Focus Coping is the patient tries directly to deal with the problems experienced, namely by doing Antiretroviral treatment, while the Emoticon Focus Coping is that the patient can make adjustments to emotional distress not excessively, namely by looking for peers and always being enthusiastic. Keywords: HIV/AIDS, Coping Mechanisms